Implementation of the Green School Festival to Increase Strengthening of Character Education in Era 4.0 - Ahmad Anis Syafi’i; Elisabeth Bengang; Fika Wulandari; Hermanus H. Ladopurab (Proceedings of The ICECRS, 2020)
The purpose of the Green School Festival is to improve character education that is held every year to manage the school as a green land that is environmentally friendly in the learning process. The research method uses qualitative descriptive data collection through observation, interviews, documentation, and descriptive qualitative analysis. The results showed nine topics that were solved for the problems that occurred. The nine topics include: publication and literacy, environmental management, waste and irrigation, liquid waste water, energy, green plants, child-friendly schools, healthy environment, and innovation and technology.